Mechanical Properties and Waste Management Approaches of Banana in India: Pharmaceutical Science-Pharmaceutics - Heena, Jindal; Tanya, Saxena; Kartik, Sawal (International Journal of Life Science and Pharma Research, 2022)
Abstract: Around 27% of the contribution to the world's banana production is done by India only. This directly leads to an increase in waste loss. Despite its tremendous utilization, nutritional & health benefits, and mechanical properties of fibres which allows the growth of the economy in the country, the problem of waste management in India is big. Usually, the leaves, pseudostems, rachis and banana peel are the major solid waste-loss of bananas which corresponds to its maintenance and harvesting practices. Its waste loss amounts to roughly 114 million metric tonnes worldwide, contributing to environmental issues such as the excessive emission of greenhouse gases. Thus, this review paper focuses on the the mechanical properties of pseudostem fibres which offer a significant bioresource to create a variety of high-value goods, including rope, cordage, fishing nets, mats, packaging materials, paper sheets, textile fabrics, bags, tablecloths, handicrafts, absorbent materials, and polymer composites. The research on banana fibre-reinforced composite materials is a new field of research and is still open to be explored. These composite-based fibres have a good potential to be used in various sectors like construction, automotive, machinery, etc., due to their high mechanical strength. Many advancements in the manufacturing techniques of its fibres are under process to ease the process. However, still, hand layup, compression moulding, and filament winding are the processes which are followed. Thus, this review paper focuses on the mechanical properties & utilization of banana pseudostem fibres and approaches to combat the main challenges of waste management and to provide sustainable solutions to achieve social, economic, and environmental benefits.